Does brand image resonance as the determinant factor in cosmetic purchasing decision? A Case Study at Sari Ayu Cosmetic - Silitonga, Parlagutan; Namira, Rai (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The research aims to propose a model that can increase customer purchase decisions and propose a series of efforts to achieve that goal. The solution proposed in this study is rooted in the R-A theory by accelerating news sharing capability. Consumers are aware of the latest developments about the product, the quality, which leads to the resonance of a company's brand image. The population in this study was the buyer of cosmetic Sariayu Martha Tilaar. The sample used in this study was 100 respondents by purposive technique. Data collection technique by accidental using the designed questionnaire. The questionnaire has been tested for its validity and reliability before distribution. The regression analysis started with the classic assumption test (normality, multicollinearity, heteroskedasticity, and linearity test) afterward by multiple linear regression analysis. The model determined by the hypotheses testing applied F test, t-test, correlation test, and the coefficient of determination. The results showed that none of the single variables stand alone. All independent variables in weak significant effect individually. Therefore, it is suggested that the Sari Ayu Cosmetic management should make a significant effort to pay attention to brand image resonance and price perception in line with the needs and wants of their potential customers.